Biochip Technology for the Serological Diagnosis of Bullous Pemphigoid. (17th December 2012) - Zarian, Haik; Saponeri, Andrea; Michelotto, Anna; Zattra, Edoardo; Belloni-Fortina, Anna; Alaibac, Mauro
Abstract : Bullous pemphigoid is an autoimmune blistering skin disease characterized by the presence of circulating autoantibodies which recognize specific proteins of the epidermis and dermoepidermal junction. Diagnosis is based on clinical criteria and laboratory investigations, notably histology, direct and indirect immunofluorescence, and ELISA. This study describes a new immunofluorescence assay for parallel determination of anti-BP180 and anti-BP230 based on recombinant antigenic substrates. The aim of the study was to detect BP180 and BP230 autoantibodies by BIOCHIP technology using both a specially designed recombinant BP180-NC16A protein and cells expressing the BP230-gc antigen fragment. 18 patients with bullous pemphigoid were included in the study. Autoantibodies to BP180 were detected by the BIOCHIP technique in 83.33% of patients with clinical, serological, and immunohistological confirmed bullous pemphigoid while autoantibodies against BP230-gC were detected only in 39% of patients. The detection of anti-BP180-NC16A and anti-BP230-gC by a new biochip-based immunoassay is a suitable alternative to indirect immunofluorescence and ELISA. This method has the advantage of easily discriminating the different autoantibody specificities. The BIOCHIP method is faster, cheaper, and easy to use when compared with the ELISA approach. For this reason, the new method could be used as an initial screening test to identify patients with bullous pemphigoid, and doubtful results could then be confirmed by ELISA.